Impacts of conventionally-treated and additionally ozonated wastewater on mortality, biochemical markers, and locomotor activity of two aquatic insect species: Leuctra geniculata (Plecoptera) and Hydropsyche incognita (Trichoptera) - Louisa E. Rothe; Nazmun Nahar; Robin Stift; Almut Gerhardt; Michael Weyand; Daniel Grabner; Christian K. Feld; Bernd Sures (Environmental Pollution, 2026)

Freshwater systems and ecosystem services: Challenges and chances for cross-fertilization of disciplines - Ágnes Vári; Simone A. Podschun; Tibor Erős; Thomas Hein; Beáta Pataki; Ioan-Cristian Iojă; Cristian Mihai Adamescu; Almut Gerhardt; Tamás Gruber; Anita Dedić; Miloš Ćirić; Bojan Gavrilović; et al. (Ambio, 2022)
Freshwater ecosystems are among the most threatened in the world, while providing numerous essential ecosystem services (ES) to humans. Despite their importance, research on freshwater ecosystem services is limited. Here, we examine how freshwater studies could help to advance ES research and vice versa. We summarize major knowledge gaps and suggest solutions focusing on science and policy in Europe. We found several features that are unique to freshwater ecosystems, but often disregarded in ES assessments. Insufficient transfer of knowledge towards stakeholders is also problematic. Knowledge transfer and implementation seems to be less effective towards South-east Europe. Focusing on the strengths of freshwater research regarding connectivity, across borders, involving multiple actors can help to improve ES research towards a more dynamic, landscape-level approach, which we believe can boost the implementation of the ES concept in freshwater policies. Bridging these gaps can contribute to achieve the ambitious targets of the EU’s Green Deal.

Continuous monitoring of avoidance behaviour with the earthworm Eisenia fetida - Nadja Rastetter; Almut Gerhardt (Journal of Soils and Sediments, 2018)

Toxic potential of different types of sewage sludge as fertiliser in agriculture: ecotoxicological effects on aquatic, sediment and soil indicator species - Nadja Rastetter; Almut Gerhardt (Journal of Soils and Sediments, 2017)

Retraction Note to: Toxic potential of different types of sewage sludge as fertiliser in agriculture: ecotoxicological effects on aquatic and soil indicator species - Nadja Rastetter; Almut Gerhardt (Journal of Soils and Sediments, 2016)

RETRACTED ARTICLE: Toxic potential of different types of sewage sludge as fertiliser in agriculture: ecotoxicological effects on aquatic and soil indicator species - Nadja Rastetter; Almut Gerhardt (Journal of Soils and Sediments, 2015)

Integrated toxicity evaluation of a pulp deposit using organisms of different trophic levels - Cornelia Kienle; Miriam Langer-Jaesrich; Daniela Baumberger; Doris Hohmann; Sergio Santiago; Heinz-R. Köhler; Daniel Zürrer; Almut Gerhardt (Journal of Soils and Sediments, 2013)

Impairment of trophic interactions between zebrafish (Danio rerio) and midge larvae (Chironomus riparius) by chlorpyrifos - Miriam Langer-Jaesrich; Cornelia Kienle; Heinz-R. Köhler; Almut Gerhardt (Ecotoxicology, 2010)

Locomotor activity and respiration rate of the ground beetle, Pterostichus oblongopunctatus (Coleoptera: Carabidae), exposed to elevated nickel concentration at different temperatures: novel application of Multispecies Freshwater Biomonitor® - Agnieszka J. Bednarska; Almut Gerhardt; Ryszard Laskowski (Ecotoxicology, 2010)

Assessing Toxicity of the Insecticide Thiacloprid on Chironomus riparius (Insecta: Diptera) Using Multiple End Points - Miriam Langer-Jaesrich; Heinz-R. Köhler; Almut Gerhardt (Archives of Environmental Contamination and Toxicology, 2010)

Can mouth part deformities of Chironomus riparius serve as indicators for water and sediment pollution? A laboratory approach - Miriam Langer-Jaesrich; Heinz-R. Köhler; Almut Gerhardt (Journal of Soils and Sediments, 2010)

Effects of 3,4-dichloroaniline and diazinon on different biological organisation levels of zebrafish (Danio rerio) embryos and larvae - Volker Scheil; Cornelia Kienle; Raphaela Osterauer; Almut Gerhardt; Heinz-R. Köhler (Ecotoxicology, 2009)

The early warning of aquatic organophosphorus pesticide contamination by on-line monitoring behavioral changes of Daphnia magna - Zongming Ren; Jinmiao Zha; Mei Ma; Zijian Wang; Almut Gerhardt (Environmental Monitoring and Assessment, 2007)

Importance of exposure route for behavioural responses in Lumbriculus variegatus Müller (Oligochaeta: Lumbriculida) in short-term exposures to Pb - Almut Gerhardt (Environmental Science and Pollution Research, 2007)

Suitability of Crangonyx pseudogracilis (Crustacea: Amphipoda) as an Early Warning Indicator in the Multispecies Freshwater Biomonitor (9 pp) - Almut Gerhardt (Environmental Science and Pollution Research, 2006)

Behavioral Changes and Acute Toxicity to the Freshwater Shrimp Atyaephyra desmaresti Millet (Decapoda: Natantia) from Exposure to Acid Mine Drainage - Luc Janssens de Bisthoven; Almut Gerhardt; Katrin Guhr; Amadeu M.V.M. Soares (Ecotoxicology, 2006)

The multispecies freshwater biomonitor a potential new tool for sediment biotests and biomonitoring - Almut Gerhardt; Stefanie Schmidt (Journal of Soils and Sediments, 2002)